2022
DOI: 10.1002/isd2.12210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of readiness for launching cloud computing services: The case of Ethio‐Telecom in Ethiopia

Abstract: A nation's telecom system plays an important role in its socio-economic development. This case study assesses the technical and organizational readiness of Ethio-Telecom to implement Cloud Computing services to serve Africa's fast-growing demand for Cloud Computing. The study used the STOPE (Strategy, Technology, Organization, People, and Environment) model as a theoretical base. A structured survey questionnaire was used to gather data from 100 mid and operational level employees. An interview was conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
3
1
0
Order By: Relevance
“…Moroccan doctors and nurses expect to improve patient access to medical services, especially in rural areas, simplify communication and relationships with patients, and increase their efficiency and productivity. This finding is consistent with the results of our previous study and other studies [ 5 , 13 , 37 41 , 56 ]. For [ 37 ] an increase in perceptions that technology is convenient can contribute to an increase in acceptance, so it is necessary to design technology solutions in a way that is convenient for users to minimize the prospects of non‐acceptance.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Moroccan doctors and nurses expect to improve patient access to medical services, especially in rural areas, simplify communication and relationships with patients, and increase their efficiency and productivity. This finding is consistent with the results of our previous study and other studies [ 5 , 13 , 37 41 , 56 ]. For [ 37 ] an increase in perceptions that technology is convenient can contribute to an increase in acceptance, so it is necessary to design technology solutions in a way that is convenient for users to minimize the prospects of non‐acceptance.…”
Section: Resultssupporting
confidence: 94%
“…It is very advisable, when implementing this technology on a large scale, to have relays at the level of public hospitals, that is, people who are worthy of respect by their entourage, and who can influence other colleagues. This finding is consistent with the results of previous studies [ 38 , 39 , 41 , 48 , 56 ]. However, this finding is not consistent with our previous study [ 5 ], in which Moroccan physicians reported that they refuse to use telemedicine technology because someone else, important or not, is using it.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations